Industry 4.0 Scorecard for SMEs - Gergin, Zeynep; Gençyılmaz, Mehmet Güney; İlhan, Doğan Aybars; Dündar, Uğurcan; Cebeci, Özay; Çavdarlı, Ali İhsan; YÜKSEKTEPE, FADİME ÜNEY; AKTİN, AYŞE TÜLİN (Springer, 2018)
Today the industry is revolutionizing into a new era with the total integration of all elements of the production through digitalization and establishing communication between each other. This new revolution is named as “Industry 4.0”. Turkey is categorized as a developing country in terms of economy and Turkish economy is ranked at 17th place in world Gross Domestic Product (GDP) ranking. The country’s economy met the expectations and reached 7.4% GDP growth in 2017 while worldwide average growth was 3.6%, and developing countries had the average of 4.6%. Turkish government encourages enterprises to keep up with industry 4.0, and KOSGEB (Small and Medium Sized Enterprises Development Organization) is supporting the SMEs with various programs. This can be seen as an opportunity for Turkish industry to catch the trend and increase its growth rapidly. And at this point the exact knowledge of the current situation is crucial. Small and Medium Sized Enter- prises (SME) has the 99.8% of the total according to Turkish Statistical Institute (TÜİK). Hence, this project is initiated to identify the current situation of SMEs of Turkish industry. A comprehensive questionnaire is prepared to find out the readiness and requirements of the SMEs for Industry 4.0 transformation. This questionnaire is applied to SMEs operating in Marmara Region of Turkey. The outcome of the research shows a scorecard for the SMEs in terms of technology usage, readiness to Industry 4.0, and also increased their awareness on the concept and the importance of the new era. The future studies are continuing as a second phase of this research in order widen the research to all regions of the country, and to develop the transformation capabilities of the selected enterprises.
Keywords: Economy; Industry 4.0; Turkish economy; Turkish industry